Dataset on applying HPMC polymer to improve encapsulation efficiency and stability of the fish oil: in vitro evaluation - Sarker, Md. Zaidul Islam; Fahim, T.K.; Ferdosh, Sahena; Azad, Abul Kalam; Rashid, M.A.; Hossain, Md Sohrab (Elsevier, 2020)
Data examines the effect of hydroxypropyl methylcellulose (HPMC) HPMC15 cP, and HPMC 5 cP polymer composition on the physicochemical traits of encapsulated oil made using lab scale spray drying (180 °C). The data found showed that the properties of the reconstituted fish oil powder are significantly affected by the polymer's composition and ratio (p < 0.05). In this experiment, powder with the particle sizes below 60 μm was produced and it was observed that HPMC is a good emulsifier for all formulations and the encapsulation efficiency is high with 75.21% for AF1 formulation. It was also observed that the process of fish oil encapsulation employed by HPMC 5 cP produce a more volatile oil powder, while encapsulation with HPMC 15 cP produced a more stable fish oil powder. These finding shows that the utilisation of HPMC as a polymer to encapsulate fish oil can produce a more efficient and stable compound.